Multi-elements atmospheric deposition study in Albania - Qarri, Flora; Lazo, Pranvera; Stafilov, Trajce; Frontasyeva, Marina; Harmens, Harry; Bekteshi, Lirim; Baceva, Katerina; Goryainova, Zoya (My University, 2014)
For the first time, the moss biomonitoring technique and inductively coupled plasma-atomic emission spectrometric (ICP-AES) analytical technique were applied to study multi-element atmospheric deposition in Albania. Moss samples (Hypnum cupressiforme) were collected during the summer of 2011 and September-October 2010 from 62 sites, evenly distributed over the country. Sampling was performed in accordance with the LRTAP Convention-ICP Vegetation protocol and sampling strategy of the European Programme on Biomonitoring of Heavy Metal Atmospheric Deposition. ICP-AES analysis made it possible to determine concentrations of 19 elements including key toxic metals such as Pb, Cd, As, and Cu. Cluster and factor analysis with varimax rotation was applied to distinguish elements mainly of anthropogenic origin from those predominantly originating from natural sources. Geographical distribution maps of the elements over the sampled territory were constructed using GIS technology. The median values of the elements in moss samples of Albania were high for Al, Cr, Ni, Fe, and V and low for Cd, Cu, and Zn compared to other European countries, but generally were of a similar level as some of the neighboring countries such as Bulgaria, Croatia, Kosovo, Macedonia, and Romania. This study was conducted in the framework of ICP Vegetation in order to provide a reliable assessment of air quality throughout Albania and to produce information needed for better identification of contamination sources and improving the potential for assessing environmental and health risks in Albania, associated with toxic metals.